Kriptosporidiosis di Indonesia - Tri Wijayanti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Cryptosporidiosis included to waterborne and soil transmited diseases, caused by Cryptosporidium, obligat intraceluller pathogen organism. Cryptosporidium cause intestinal infection of human and animal acute diarrhea. Lung cryptosporidiosis on HIV/AIDS and tuberculosis patients was reported. Diarrhea still be important health problem because diarrhea was be the third dominant contributor of children morbidity and mortality at some country include Indonesia. Every children have 1,6-2x diarrhea onset annually. Diarrhea cases caused by Cryptosporidium sp parasite was around 4-11%. Focus of this review is about cryptosporidiosis on children, HIV/AIDS and tuberculosis patients, animal, environment, diagnostic and it’s prevention and control. Cryptosporidium species confirmed in Indonesia are C. wrairi, C. muris, C. felis, C. hominis, C. meleagridis and C. parvum, indicated that there was a big rule of animal on Cryptosporidium transmission. Cryptosporidium was necessary to be one of diseases diagnose on HIV/AIDS and tuberculosis patients. Transmission of Cryptosporidium by respiratory secretion (droplet, aerosol or contact with vomiting) must be anticipated to prevent cryptosporidiosis especially on imunocompromissed/imunodeficiency people. Rapid Diagnostic Test that have highly sensitivity and spesificity is very important on Cryptosporidium cases finding and surveillance in Indonesia. Environment and cattle sanitation, personal hygiene, water and food treatment, is necessary to prevent cryptosporidiosis transmission.